LEXICAL REPETITIONS IN THE POETRY OF USMON AZIM - Umid Egamov (Western European Studies, 2024)
Artistic and visual means play an extremely important role in drawing the attention of students to the events that have found their artistic expression in poetic speech and in revealing the poetic value. In particular, through lexical repetitions, the imagery becomes more vivid, the artistic and stylistic meaning increases, the poet's current mental state and experiences, growth and changes in his complex nature, and most importantly, the artisticaesthetic, psychological rediscovery of the world. is mounted. Types of repetition such as anaphora, repetition, repetition, epiphora are also an integral and important link of the poet Usman Azim's poetry. Similarly, repetition is the only tool of artistic conditioning and allows the poet to understand the essence of the literary world, the conflict between words and spirit. If the poet aims to create an artistic expression of the essence of the universe and man in general, he will definitely pay attention to the existing reality and content carefully. In this article, the linguopoetic features related to lexical repetitions in Usman Azim's poetry are studied, and the importance of lexical repetitions is discussed in it. Usman Azim's poems serve as illustrative material of the article
Keywords: lexicon; words; word forms; anaphora